2009
DOI: 10.1002/clc.20321
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Thrombosis and Hemostasis in Acute Coronary Syndromes: Relationship to Increased Heart Rate and Reduced Heart‐Rate Variability

Abstract: Background: Acute coronary syndromes (ACS) are characterized by abnormal heart-rate variability (HRV) and biomarkers of endothelial damage and thrombosis. Hypothesis: We hypothesized an association between these factors in patients with ACS. Methods: We studied 99 patients with ACS measuring HRV and plasma markers of endothelial damage/dysfunction (von Willebrand factor, vWF) and thrombosis/hemostasis (soluble P-selectin (s-Psel); CD 40 -ligand (CD 40 -L); D-dimer). HRV and plasma indices were compared to age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The plasma vWF levels of two genotypes (AG and GG) in the experimental group were higher than their corresponding levels in the control group. The results may be associated with a higher risk of vascular endothelial injury in patients with coronary heart disease, resulting in more vWF being released by the endothelial cells into the plasma (13).…”
Section: Discussionmentioning
confidence: 99%
“…The plasma vWF levels of two genotypes (AG and GG) in the experimental group were higher than their corresponding levels in the control group. The results may be associated with a higher risk of vascular endothelial injury in patients with coronary heart disease, resulting in more vWF being released by the endothelial cells into the plasma (13).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the relationship between CV activity and haemostatic variables in patients. For example, a recent study observed a lower resting heart rate variability in patients with acute coronary syndrome who also showed increased levels of von Willebrand factor, soluble P-selectin and D-dimer compared to healthy subjects, but did not detect correlations between different indexes of heart rate variability and these thrombotic/haemostatic markers 26 . Other studies have found that the power of a high frequency component of heart rate variability (HF-HRV) obtained during 24-hour monitoring was inversely associated with both a composite prothrombotic index and individual levels of haemostatic factors, including von Willebrand factor antigen (VWF:Ag), activated clotting factor VII, fibrinogen, plasminogen activator inhibitor-1 (PAI-1), and mean platelet volume (MPV) 27 28 .…”
mentioning
confidence: 93%
“…15.8, separated by placebo, serpin treatment and dosage, and time to follow-up. DD has been correlated with inflammatory, unstable coronary syndromes (ACS), as well as with pulmonary emboli (Empana et al ., 2008; Hamaad et al ., 2009) and is a by-product of fibrin degradation (fibrinolysis), the pathways targeted in part by the serpin treatment.…”
Section: Assessing Clinical Therapeutic Potential For a Viral Serpmentioning
confidence: 99%